Smelting Separation Behaviors and Mechanisms of High-Alumina Rich-Manganese Ore Obtained from Metallic Reduction and Magnetic Separation - Lihua, Gao; Liu, Zhenggen; Chu, Mansheng (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The smelting separation of high-alumina rich-manganese ore prepared with selective reduction and magnetic separation was proposed to produce the high carbon ferromanganese alloy (HCFeMn) in this paper. The rational smelting separation parameters for high-alumina rich-manganese ore includes a FC/O of 1.1, a smelting temperature of 1550°C, a melting time of 60 min, and a basicity of 0.7. The smelting separation of high-alumina rich-manganese ore was achieved successfully. The content of Fe, C, Si and other impurities (P, S) are 12.13%, 6.73%, 0.17% and 0.14, 0.008, respectively. Especially, the recovery and content of Mn reach around 80.47% and 76.76%. The obtained high carbon ferromanganese alloy has met the higher standard (FeMn78C8) of ferromanganese alloy, especially, the content of Si P and S in the HCFeMn alloy is far below the standard value. Based on the SEM-EDS, XRD and thermodynamic calculation, the smelting and separation mechanisms of high-alumina rich-manganese ore was proposed to more effectively explain the effect of smelting parameters on slag/metal separation behaviors during the process of smelting HCFeMn alloys.